GROWTH PERFORMANCE OF THREE NATIVE TREE SPECIES FOR PULPWOOD PLANTATION IN DRAINED PEATLAND OF PELALAWAN DISTRICT, RIAU - Junaedi, Ahmad (Association of Indonesian Forestry and Environment Researchers and Technicians, 2018)
The productivity of exotic species developed in pulpwood plantations in Indonesia (HTI-pulp) has been continuously decreasing. On the other side, there is a possibility to develop several promising native tree species in peatland HTI-pulp plantations. However, less information is available on the performance of those native tree species for planting in peatland pulpwood plantation. This study evaluates the performances (survival rate, growth and yield) of three native trees [mahang (Macaranga pruinosa), skubung (Macaranga gigantea) and geronggang (Cratoxylum arborescens)] in drained peatland, in terms of suitability for pulpwood plantation. An experiment plot was established by planting three native tree species and krasikarpa (Acacia crassicarpa) in drained peatland at Pelalawan District, Riau. Survival, growth and yield variables were monitored frequently until 5.5 years after planting (YAP) and then were analyzed. Geronggang (survival rate = 80.0%) and mahang (survival rate = 65.6%) showed good survival rates at 5.5 YAP which were significantly (p<0.05) higher than that of krassikarpa (22.4%). Geronggang and mahang are relatively promising growth and yield in which height, diameter and yield increment until 5.5 YAP were 1.96 m/year and 2.31 m/year; 2.08 cm/year and 2.59 cm/year; 13.1 m3/ha/year and 21.4 m3/ha/year, respectively. Yet, those growths and yields were still significantly (p<0.05) lower than those of krasikarpa, probably due to unequal seedling quality. These results indicated the potential of mahang and geronggang to be developed in peatland pulpwood plantations. However, tree improvement program is necessarily required for mahang and geronggang to initiate the development.